Lean supplier development : establishing partnerships and true costs throughout the supply chain - Harris, Chris , 1976-; Harris, Rick , 1953-; Streeter, Chuck (Productivity Press, 2011)
Applies the concept of value mapping to the efficient designing of a supply chain. This book shows how to analyze and map the total supply chain process, assessing any gaps or redundancies that waste time. It considers the complexity of multiple suppliers, distribution centers, and dispersed customers